Commodity Price Shocks And Macroeconomic Performance In Sub-Saharan Africa - Sanya , Ogunsakin (Archives of Business Research, 2020)
This study investigated the relationship between commodity price shocks and output growth in Sub-Saharan African countries using panel data which covered the period between 2005 and 2017. Data for the study were sourced from the World Development Indicators (WDI). Data base of the World Bank, The IMF’S International Financial Statistics (IFM) and Publications of Central Banks of various countries selected. The study employed Generalized Movement Average (GMM) as the estimation technique. Findings from the study showed that positive changes in the prices of export commodities has little positive impact on macroeconomic performance in Sub-Saharan Africa while negative price change has negative and significant impact on macroeconomic performance in Sub-Saharan African countries during study period. Based on these findings, the study therefore concludes that the relationship between commodity price shocks and macroeconomic performance in Sub-Saharan Africa is asymmetric. The study recommends that countries in Sub-Saharan Africa should introduce and implement policies to withstand shocks that may come from commodity price shocks such as economic diversification not only in area of agriculture but also in the area of industrialization and manufacturing.